2010
DOI: 10.1093/protein/gzq009
|View full text |Cite
|
Sign up to set email alerts
|

Reduced elimination of IgG antibodies by engineering the variable region

Abstract: Fc engineering to increase the binding affinity of IgG antibodies to FcRn has been reported to reduce the elimination of IgG antibodies. Herein, we present a novel non-FcRn-dependent approach to reduce the elimination of IgG antibodies. Pharmacokinetic studies conducted in normal mice of various humanized IgG4 antibodies, which had identical constant regions but different variable region sequences, revealed that an antibody with a lower isoelectric point (pI) has a longer half-life. These antibodies exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
220
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(228 citation statements)
references
References 38 publications
6
220
2
Order By: Relevance
“…This fast clearance in mice could be due to the high isoelectric point of the mAb (pI = 9.2), a parameter that has been shown to negatively affect half-life and clearance. 45 In this set-up, all IgG variants displayed substantial serum half-life increase with ratios (half-life variant/WT) between 1.8 and 2.8. 25 Similarly, IgG-YTE had a ratio between 2.3 and 3.3, slightly lower than the published values of ~3.8.…”
Section: Serum Persistence In Human Fcrn Transgenic Micementioning
confidence: 81%
See 1 more Smart Citation
“…This fast clearance in mice could be due to the high isoelectric point of the mAb (pI = 9.2), a parameter that has been shown to negatively affect half-life and clearance. 45 In this set-up, all IgG variants displayed substantial serum half-life increase with ratios (half-life variant/WT) between 1.8 and 2.8. 25 Similarly, IgG-YTE had a ratio between 2.3 and 3.3, slightly lower than the published values of ~3.8.…”
Section: Serum Persistence In Human Fcrn Transgenic Micementioning
confidence: 81%
“…In addition, other factors than FcRn binding have been shown to influence PK of natural mAbs: overall protein structure, glycosylation status, isoelectric point, 45 methionine oxidation, 59 interaction with the target but also specificity. Indeed, mAbs with the same wild-type human Fc sequences but different Fv domains were shown to bind FcRn with considerable differences.…”
Section: Discussionmentioning
confidence: 99%
“…antibody stability and variability in antigen distribution) also play a role in determining the ultimate PK outcome of an engineered antibody. In this regard, we do envision that extremely long half-lives of Fc-containing molecules could be achieved by combining FcRn binding engineering with FcRn-independent half-life-extending technologies, such as pI optimization (39) and pH-dependent antigen binding engineering (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…12,18,[38][39][40] These results are also consistent with a similar study using the IgG4 isotype, in which a higher pI led to a shortened half-life and higher clearance rates regardless of presence of FcRn. 15 Studies on larger sets of antibodies suggest that the correlation between pI and clearance rates is not generalizable; 24,25 however, a localized patch of positive charge may be sufficient to increase interactions with the negatively charged surface of cell membranes. Nonspecificity driven clearance is not solely charge dependent, and other factors, including hydrophobicity, have been implicated in driving accelerated clearance rates.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14] In addition to Fc engineering efforts, multiple studies have reported disparate PK parameters in antibodies with identical Fc regions but different variable regions. [15][16][17][18][19][20] In particular, clearance rates are increased in antibodies with polyreactive [21][22][23] or cross-reactive 24,25 profiles.…”
Section: Introductionmentioning
confidence: 99%